2023
DOI: 10.1039/d3nj01963b
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nitrogen-deficient g-C3N4 nanosheets via an acetaldehyde-assisted hydrothermal route and their high photocatalytic performance for H2O2 production and Cr(vi) reduction

Abstract: A highly nitrogen-deficient g-C3N4 (AH-CN) nanosheets material was successfully prepared by acetaldehyde assisted hydrothermal route. The as-prepared AH-CN material was analyzed by a series of X-ray powder diffraction (XRD), N2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…By comparing the above two schemes of the photocatalytic reduction of Cr( vi ), the former is obviously superior to the latter. In addition, the photocatalytic reduction of Cr( vi ) has been compared with the previous reports, 63,64 as shown in Table S4 †. Interestingly, compounds 1–4 have good characteristics as catalysts for the photocatalytic reduction of Cr( vi ).…”
Section: Resultsmentioning
confidence: 91%
“…By comparing the above two schemes of the photocatalytic reduction of Cr( vi ), the former is obviously superior to the latter. In addition, the photocatalytic reduction of Cr( vi ) has been compared with the previous reports, 63,64 as shown in Table S4 †. Interestingly, compounds 1–4 have good characteristics as catalysts for the photocatalytic reduction of Cr( vi ).…”
Section: Resultsmentioning
confidence: 91%
“…After the introduction of N/O vacancies, the absorption edge broadens to 410 and 506 nm, respectively, consistent with previous reports. 58,59 Upon the formation of heterojunctions, the absorption edges of CNS/BOCB and CNS/BOCB-OV are respectively located between their two components.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ultrasonication step in acid media, performed in the synthesis of 500-AUCN, resulted in a reduction in the number of N 2C atoms relative to N 3C atoms when compared to 500-UCN and 500-CN, leading to the creation of N vacancies that enhance its photocatalytic performance [ 64 , 118 ]. It has been reported that a higher concentration of nitrogen vacancies improves the separation of photogenerated charge carriers and light absorption [ 119 , 120 ]. Furthermore, N 3C has a larger number of unpaired electrons in the nitrogen atoms, resulting in a higher density of active sites available for photocatalytic processes [ 121 ].…”
Section: Resultsmentioning
confidence: 99%